PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP RETURN SAHAM PADA SEKTOR PERTAMBANGAN DI BEI PERIODE 2014-2017 - Manse, Christya Ayu (Buletin Ekonomi, 2018)
A good company can be seen from its financial statements, without financial statements, the company or managers will experience difficulties in analyzing the conditions and position of the company, managers will also not to evaluate how high the level of success of the company in stock returns and make teh best decisionss to make the company continues to progress and develop in the future. The purpose of my thesis was to see influence of managerial ownership, institutional ownership, independent board of directors, and the board of directors partially and simultaneously on the company's stock returns in the mining sector on the ISE 2014-2017 period. Sampling in this study was conducted by purposive sampling technique, namely by determining certain criteria required by the writer in sampling, so that the samples obtained in my thesis were 12 companies from 41 populations of mining companies on the ISE for the 2014-2017 period. Data analysis techniques used in this study are descriptive statistics, classical assumption tests, hypothesis testing (t test and F test), and multipel linier regression tests. The result of t test in this study obtained a significant value of managerial ownership greater than the significant level that has been determined (0.113> 0.05). Significant value of institutional ownership is greater than the significant level that has been determined (0.458> 0.05). The significant value of the independent board of commissioners is smaller than the significant level that has been determined (0.020> 0.05). The Board of Directors is greater than the significant level that has been determined (0.259> 0.05). The results of F test in this study obtained significant value greater than the significant level that has been determined (0.143> 0.05), this shows that managerial ownership, institutional ownership, independent board of directors, and board of directors have no effect on the company's stock returns in the sector mining on the ISE for the 2014-2017 period. Keyword: good corporate governance, stock return.